Prevalence and determinants of radiological vertebral fractures in patients with Klinefelter syndrome. (21st July 2020) - Vena, Walter; Pizzocaro, Alessandro; Indirli, Rita; Amer, Myriam; Maffezzoni, Filippo; Delbarba, Andrea; Leonardi, Lorenzo; Balzarini, Luca; Ulivieri, Fabio M.; Ferlin, Alberto; Mantovani, Giovanna; Lania, Andrea G.; et al.
Abstract: Background: Klinefelter syndrome (KS) may induce skeletal fragility, but the studies so far published on this topic were mainly focused on the evaluation of bone mineral density (BMD) and bone microstructure, whereas data on fracture risk are still lacking. Objective: To evaluate the prevalence and determinants of vertebral fractures (VFs), that is, the hallmark of osteoporosis, in subjects with KS. Materials and methods: Eighty‐seven patients with KS (median age 41 years, range 18‐64) were consecutively evaluated for radiological VFs (by quantitative morphometry) and lumbar spine and femoral neck BMD (by DXA). Fifty‐five patients with KS were also evaluated by the fracture risk assessment (FRAX) tool. Results: Low BMD was found in 22/87 (25.3%) patients [12 with osteopenia, three with osteoporosis and seven with "low BMD per age" (subject < 50 years with Z ‐score ≤−2.0 SD)] and VFs in 13/87 (14.9%) patients. In patients with VFs, the median spine deformity index was 2 (range 1‐9). Prevalence of VFs was similar between healthy and low‐BMD patients (15.9% vs 13.6%; P  = .80). Noteworthy, patients with VFs had significantly higher age at diagnosis of KS as compared to patients who did not fracture ( P  = .039), without significant differences in age at the time of observation ( P  = .162), body mass index ( P  = .234), testosterone replacement therapy ( P  = .432), duration of testosterone therapy ( P  = .409), vitamin D therapy ( P  = 681), and serum testosterone levels ( P  = .338). Moreover, patients with VFs were more likely to complain back pain in comparison with those without VFs (33.3% vs 7.4%; P  = .047). In 55 cases evaluated by the FRAX® tool, no significant differences in 10‐year risk of major fracture ( P  = .270) and hip fracture ( P  = .860) were found between fractured and non‐fractured patients. Conclusions: This study provides first evidence that KS may be associated with risk of VFs in close relationship with delay in disease diagnosis but independently of BMD values and serum testosterone levels or testosterone therapy.